SUPERVISI AKADEMIK KEPALA SEKOLAH PADA SMA NEGERI 1 SUNGAI TEBELIAN KABUPATEN SINTANG - Mayor, A.; M. Amin, H. Maswardi; ., Masluyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThe purpose of this research is to know, understand, discuss in detail aboutthe planning program, the implementation, andthe follow up of the academic supervision conducted by the principal of SMA Negeri1 Sungai TebelianÂ Sintang. This research uses qualitative approach. As the subject of research is the principal, the vice principal, the four senior teachers,and eleven non-civil servant teachers.The data were collected by using observation, interview, and documentation techniques. The results of this study found that the planning program conducted bythe principal, vice principal, and the senior teachers did not involve all the related components that affected thesuccessfulness of the academic supervision program.The implementation of the academic supervision involved the principals and the senior teachers. The followup of the supervision is just for guiding and strengthening toward teachers. Based on the result sabove, the principalâ€™s academic supervision has not been achieved effectively to improve the better results of teaching.Keywords: Supervision Academic, Principal